2022
DOI: 10.32677/ijch.2017.v04.i02.007
|View full text |Cite
|
Sign up to set email alerts
|

Rodenticide poisoning in children: A study of clinical profile and electrocardiographic changes

Abstract: Objectives: To study the clinical profile and electrocardiographic (ECG) changes in rodenticide poisoning in children. Methods: Patients admitted with a history of ingestion of rat poison between October 2014 and October 2016 were included in the study. Clinical history was taken in detail, and stomach wash samples were sent for toxicological analysis. Continuous ECG monitoring was done in all cases. Investigations to assess organ functions and coagulation profile were done at admission and repeated as indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
3
3
1
Order By: Relevance
“…In a few studies in India, a few instances of homicidal YP poisoning have also been reported. 9,10 In other studies, similar age group preponderance was observed. 9 Children easily mistake YP paste for toothpaste and consume it.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In a few studies in India, a few instances of homicidal YP poisoning have also been reported. 9,10 In other studies, similar age group preponderance was observed. 9 Children easily mistake YP paste for toothpaste and consume it.…”
Section: Discussionsupporting
confidence: 76%
“…9,10 In other studies, similar age group preponderance was observed. 9 Children easily mistake YP paste for toothpaste and consume it.…”
Section: Discussionsupporting
confidence: 76%
“…In a study on ECG changes on rodenticide poisoning by Soltaninejad et al, the ECG changes or cardiovascular symptoms appeared between 3 and 5 h after admission [9]. In a study by Sugunan et al, the mean time of onset of ECG changes is 19.7 h [10]. In our study, the average time interval between intake of poison and the appearance of ECG findings was 22 h.…”
Section: Methodssupporting
confidence: 51%
“…At pH 4, 7.1% of zinc phosphide hydrolyzed in 12 hours, whereas 38.8% hydrolyzed at pH 2 over the same period. 7 Yellow phosphorus (white phosphorus) is commonly available as a paste which is spread over bait. "RATOL" is the most popular brand.…”
Section: Introductionmentioning
confidence: 99%